PENGEMBANGAN ALAT UKUR KETERAMPILAN DASAR BERMAIN SOFTBALL - KS, Sugiyanto (LPMPP Universitas Negeri Yogyakarta, 2010)
Abstract: Developing Instruments to Measure Basic Softball Skills. This studyaims to develop instruments to measure basic softball skills and to test their validityand reliability. This study shows that (1) the result of overhand throwingmeasurement test is (rxx= 0.704), (2) the sidearm throwing is rxx = 0.604, and (3) thestriking skill is rxx = 0.050. It can be concluded that the instrument to measure thethrowing-striking basic skill has satisfied the validity and reliability criteria, and theone to measure the striking basic skill is valid although its reliability is low. It issuggested that (1) a variety of instruments should be developed to measure avariety of skills, and (2) all practitioners are expected to develop othermeasurement instruments not covered in this study.Keywords: measurement instruments, basic skills, softball